Effects of land use on water quality and Ceriodaphnia dubia reproduction - García-García, Patricia L.; Martínez-Jerónimo, Fernando; Vázquez, Gabriela; Favila, Mario E.; Novelo-Gutiérrez, Rodolfo (HIDROBIOLÓGICA, 2017)
This study evaluated the effect of water quality of streams from micro-watersheds with different land use (cloud forest, coffee plantation, pasture and under urban influence) during the dry and rainy seasons, lying within the upper watershed of the La Antigua river in Veracruz, Mexico. Water characteristics were measured and laboratory subchronic toxicity tests were performed to evaluate average accumulated progeny, broods per female, and non-reproductive females of Ceriodaphnia dubia. The cloud forest contained chemically undisturbed streams, while the lowest levels of chemical alteration were detected in pasture streams: low fecundity of C. dubia was observed in both types of streams. The most disturbed streams were those associated with coffee plantations and under urban influence, which resulted in enhanced C. dubia fecundity; however, the highest chemical disturbance, found in a stream with urban influence, led to reproduction suppression in the dry season. The most favorable conditions for reproduction were provided by nutrient and probably organic enrichment in streams associated with urban environments and coffee plantations, while in cloud forest and pasture streams, the natural, and close to natural water chemistry caused a reduction in fecundity. Female fecundity was higher during the rainy season.